COMMUNITY BELIEFS ON ANIMAL SIGNALLING: EVIDENCE FROM WEST PAPUAN TRIBAL GROUPS - Deny Anjelus Iyai; Yubelince Yustenci Runtuboi; Vapriel A. Pattikawa; Stepani F. Haryati; Azchar Prianka P.; Rizki Prasetya; Meky Sagrim; Fitri A. Arief; Ferawati R. Runtuboi; Riskayanti Riskayanti; Ditasari Amalia; Juni C. Dami; Stepanus Pakage (BIOTROPIA, 2026)
ARTICLE HIGHLIGHTS Indigenous communities read animal signs as early warnings for nature events Shared experiences shape how different animal behaviours gain meaning Local wisdom shows animals as sensitive partners in human survival   ABSTRACTObserving animal behavior and daily activities can help humans gain knowledge and derive practical benefits. A mixed-method approach, combining desk-based study and telephone interviews, was employed to collect data from seven major Papuan tribal groups. The desk study involved the collection of approximately 2,000 references published between 1980 and 2020 using keyword-based searches conducted with specialized software. Data were also provided by leaders from the seven major communities. The collected data were analyzed using Rayyan, VoS Viewer, Crammer’s Phi, and Microsoft Excel. The principal findings indicate that 14 publications addressed topics related to animal signaling and community beliefs. The animals recognized by the seven major tribal group as exhibiting signals included mammals (52%), fish (8%), reptiles (12%), amphibians (8%), birds (4%), and insects (16%). Animals were reported to convey signals through vocalizations (sounds), appearance, body parts, wastes, tracks, constructed objects, and odors. The result of Crammer’s Phi analysis showed (168) = 219.48, P = 0.0046, df = 168,  = 0.05 and 0.01, and φc = 0.0105 (1%). This results indicate a significant association between perceived values in interpreting animal signals and tribal community groups in West Papua. A Cartesian graph demonstrated low-to-high levels of both animal signaling and beliefs. Beliefs and practices related to animal sensitivity and communication vary across cultures and communities worldwide. Many indigenous communities maintain a deep spiritual connection with nature and animals, viewing them as sentient beings with their own forms of communication and sensitivity.